2006
DOI: 10.1111/j.1432-2277.2006.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tacrolimus, cyclosporin A and sirolimus on MG63 cells

Abstract: Summary The reduction in bone mineral density after organ transplantation results in increased morbidity (post‐transplantation bone disease) and remains an unsolved problem. A connection with the long‐term application of nonglucocorticoidal immunosuppressants is the subject of controversial discussion. We hypothesized that such substances have an influence on the skeletal system on the cellular level by modulating osteoblast differentiation. Therefore, we investigated the effects of tacrolimus, cyclosporin A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…In patients with chronic renal failure and secondary hyperparathyroidism that have undergone renal transplantation, it is expected that there is a greater production in the first trimester after transplantation, until osteoblasts become inactive and bone metabolism is suppressed. It has been reported that corticosteroids, calcineurin inhibitors, and mTOR inhibitors stimulate FGF-23 production [9, 10], even though in the first months after transplantation, with the use of higher doses of these drugs we as well as others observed the greater reduction [3–6]. Furthermore, hypophosphatemia which is the major stimulant for FGF-23 secretion is resolved.…”
Section: Discussionmentioning
confidence: 90%
“…In patients with chronic renal failure and secondary hyperparathyroidism that have undergone renal transplantation, it is expected that there is a greater production in the first trimester after transplantation, until osteoblasts become inactive and bone metabolism is suppressed. It has been reported that corticosteroids, calcineurin inhibitors, and mTOR inhibitors stimulate FGF-23 production [9, 10], even though in the first months after transplantation, with the use of higher doses of these drugs we as well as others observed the greater reduction [3–6]. Furthermore, hypophosphatemia which is the major stimulant for FGF-23 secretion is resolved.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly to NRapamycin and derivatives (excepted tacrolimus) also influence bone tissues. Indeed, mTOR appears as an essential signalling pathway engaged in the stimulation of osteoclast survival [79] and affects osteoblast differentiation [80]. Tumour Necrosis Factor-α (TNF-α), Receptor Activator of Nuclear Factor κB Ligand (RANKL) and Macrophage-Colony Stimulating Factor (M-CSF) promote osteoclast survival by signalling through mTOR/S6K [70].…”
Section: The Compounds Derived From Rapamycinmentioning
confidence: 99%
“…Finally, it should be noted that successful kidney transplantation usually tends to lower the markedly increased FGF23 concentrations so often seen in advanced stages of CKD [74,75,76,77]. The results of some clinical studies suggest that despite the rapid decline in plasma FGF23 concentration after kidney transplantation, it is still slightly but significantly higher than in the general population [77].…”
Section: Factors Influencing Plasma Fgf23 Concentrationmentioning
confidence: 99%
“…The results of some clinical studies suggest that despite the rapid decline in plasma FGF23 concentration after kidney transplantation, it is still slightly but significantly higher than in the general population [77]. This could be attributed to the common use of phosphate supplementation or active vitamin D treatment of the post-transplant hypophosphatemia [74,78], but may also be related to the observations that calcineurin inhibitors and sirolimus in fact stimulate FGF23 production [75,76]. On the other hand, no differences in the plasma concentration of FGF23 between the post-transplant and CKD population with equal eGFR have been found [74].…”
Section: Factors Influencing Plasma Fgf23 Concentrationmentioning
confidence: 99%